The Impact of Neurodynamic Mobilization and Transcutaneous Electrical Nerve Stimulation on Pain Intensity in Cigarette Company Workers at Risk of Carpal Tunnel Syndrome - Utami, Kurnia Putri; Astuti, Tri Ayu; Lubis, Zidni Imanurrohmah (KnE Medicine, 2022)
Indonesia is one of the largest cigarette producers and consumers in the world. Due to the repetitive activity and long hours experienced by cigarette manufacturer workers who roll the cigarettes, the risk of carpal tunnel syndrome (CTS) is high. They tend to experience pain, numbness and tingling through the hands and fingers. These symptoms occur following compression of the median nerve, which affects their functional ability. Neurodynamic mobilization (NDM) and transcutaneous electrical nerve stimulation (TENS) have been used as physical therapy in management of CTS. However, no studies have yet investigated the effect of the combination of both treatments and compared them. This was a quasi-experimental study with a pre-test post-test design, which compared the effect of a combination of NDM and TENS versus NDM only with cigarette company workers. The workers with the risk of CTS were divided into two groups: the combination NDM with TENS group and the NDM group. The interventions were applied 3 times a week for 1 month in both groups. The visual analogue scale (VAS) was used to measure the pain. The VAS scores were evaluated on the first day before the interventions were given and after 1 month. The Wilcoxon test was used to assess pre and post treatment. The Mann Whitney test was used to compare the effects of both interventions. According to the findings, both groups had a significant change in VAS measurement outcomes. The decrease in pain was larger in the NDM and TENS group than in the NDM group (p = 0.008). Carrying out a combination of NDM with TENS 3 times in a week for 1 month had a substantial impact on decreasing pain in cigarette workers with CTS risk Keywords: neurodynamic mobilization, TENS, carpal tunnel syndrome, pain, cigarette workers